Pelaksanaan Supervisi Akademik Berbasis Coaching Terhadap Kinerja Guru di UPT SPF SD Negeri 3 Kasimpureng - Muhammad Arfin; Munirah, Munirah; Nurlina (Prosiding SISFOTEK, 2024)
This study aims to determine teacher performance through the implementation of coaching-based academic supervision by school principals. The subjects in this study were principals and teachers of UPT SPF SD Negeri 3 Kasimpureng. This research used descriptive method with qualitative approach. Data collection techniques were interview, observation and documentation study. Data were analysed using reduction, presentation and conclusion techniques. The results showed: (1) The coaching-based academic supervision programme is made based on one of the school's strategic plans, namely improving teacher performance in managing effective learning; (2) The implementation of coaching-based academic supervision uses practical, objective, humanist, sustainable and constructive principles through approaches and techniques based on teacher characteristics; (3) School principals provide guidance and coaching, then teachers are recommended to attend training, technical assistance, and competency improvement workshops; (4) Supporting factors for coaching-based academic supervision are teachers‘ willingness to learn, teachers’ good perception of coaching-based academic supervision, principals' knowledge, and harmonious relationships among school members. The obstacles in coaching-based academic supervision are the principal's sudden external activities that disrupt the supervision schedule. There are no senior teachers who can assist the principal. Teachers were unable to attend the scheduled class visits.